Greetings from Trinidad, B.W.I. - Chan's Photographers (My University, 2009)
This is a multi view postcard showing Piarco Airport, Kent House and The Pitch Lake. A handwritten correspondence is visible and a 12 cents Trinidad and Tobago postage stamp.
Colour: Black and White; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Airports--Trinidad and Tobago; Pitch Lake, The